Addressing the unmet needs of patients with BRAF-mutated melanoma in Latin America: Expert perspective - Salman, Pamela; de Melo, Andreia Cristina; Rico-Restrepo, Mariana; Rodriguez, Jeronimo; Russi, Andrea; Schmerling, Rafael Aron; Zambrano, Angela; Cinat, Gabriela (Frontiers in Oncology, 2023)
Melanoma represents an increasing public health burden with extensive unmet needs in Latin America (LA). The BRAF mutation is present in approximately 50% of all melanomas in White populations and is a target of precision medicine, with the potential to dramatically improve patient outcomes. Thus, increased access to BRAF testing and therapy in LA must be explored. At a multi-day conference, a panel of Latin American experts in oncology and dermatology were provided with questions to address the barriers limiting access to testing for BRAF mutation in patients with melanoma in LA, who may be eligible for targeted therapy to improve their prognosis. During the conference, responses were discussed and edited until a consensus on addressing the barriers was achieved. Identified challenges included ignorance of BRAF-status implications, limited human and infrastructural resources, affordability and reimbursement, fragmented care delivery, pitfalls in the sample journey, and lack of local data. Despite the clear benefits of targeted therapies for BRAF-mutated melanoma in other regions, there is no clear path to prepare LA for a sustainable personalized medicine approach to this disease. Due to melanoma’s time-sensitive nature, LA must aim to provide early access to BRAF testing and consider mutational status within treatment decision-making. To this end, recommendations are provided and include establishing multidisciplinary teams and melanoma referral centers and improving access to diagnosis and treatment.